DEVICE, METHOD, AND PROGRAM FOR CALCULATING RISK INDEX OF MILD COGNITIVE DISORDER - MASUYAMA HIROAKI; OKUMA KANA; HATAYAMA KOTA; HASUKO KAZUMI (2024)
To provide a technique of calculating the risk of a mild cognitive disorder for a subject who handed in a stool sample and an inquiry.SOLUTION: The device for calculating the risk of a mild cognitive disorder includes: an extraction unit for extracting second data on a factor or an enteric microorganism which suggests a connection with a mild cognitive disorder from first data on gut flora of a subject; and a calculation unit for inputting the second data into a model which calculates the possibility that the subject is having a mild cognitive disorder by using, as a variable, third data on one or plural enteric microorganisms showing the difference between the gut flora of a healthy person and the gut flora of a person who is having the mild cognitive disorder, and calculating the risk of the mild cognitive disorder of the subject.SELECTED DRAWING: Figure 1 【課題】 便検体及びアンケートを提出した被検者に対し、軽度認知障害に対するリスクを算出する技術を提供する。【解決手段】被検者の腸内微生物叢に関する第１のデータから、軽度認知障害との関連が示唆される因子又は腸内微生物に関する第２のデータを抽出する抽出部と、健康な人の腸内微生物叢と前記軽度認知障害に罹患している人の腸内微生物叢との違いを示す１つ又は複数の腸内微生物に関する第３のデータを変数として、前記被検者が前記軽度認知障害を有する確率を算出するモデルに、前記第２のデータを入力し、前記被検者の前記軽度認知障害に対するリスクを算出する算出部と、を備える軽度認知障害のリスク指標算出装置。【選択図】 図１